Incorporating physical activity‐based interventions in school psychology research and practice: A systematic review. Issue 6 (21st March 2019) - Greenspan, Scott B.; Fefer, Sarah A.; Whitcomb, Sara A.; Kemp, Jessica M.
Abstract: Physical activity provides a myriad of well‐documented social‐emotional, behavioral, and academic benefits for youth. While research suggests that physical activity should be integrated within the school day to support the well‐being of students, an understanding of related empirical work within school psychology research and practice is unclear. School psychologists are well positioned to systematically incorporate physical activity within their intervention practices, particularly given their role and expertise in implementing and evaluating interventions. Authors engaged in a systematic review of 20 years (1998–2018) of physical activity intervention research within 10 peer‐reviewed school psychology journals and six school psychology‐related journals. Authors analyzed 22 studies to glean a comprehensive understanding of the literature base and highlight the ways in which physical activity can be incorporated to support school and student outcomes. Suggestions for research and practice in school psychology are discussed in light of the examined literature.